Consumer's motivations to used self service kiosk in fast food restaurant/ Harnidah Samengon - Samengon, Harnidah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The rapid growth in information and communication technology (ICT) has enabled hospitality operations to use a range of technologies to facilitate service to the consumer and to optimize consumer experience and satisfaction. Self Service Technology (SST) is one ICT that enables consumers, without or at least with the assistance of employees or service providers to build service. The kiosk is one used commonly by SST. Restaurants utilize self-service kiosks (SSK) for consumers to locate, configure and do the payment for their food and drink orders and have been widely utilized by the fast-food restaurant to lowered the expense of personnel, increased processing quality and the precision of orders, boosted upsell sales and is typically an appealing choice for millennial consumer and younger workers. Several pieces of research have helped to understand why consumers are choosing SSK, describing the different factors that affect the preference. Most of previous research on the adoption of technology over focus on adoption factors in the trial stage and the usage of student samples. Thus, this study explores the motivations of consumer which focus on millennial between 18 to 34 years old in using SSK in a fast-food restaurant. This qualitative research obtained the data from interview sessions with informants from the consumers of fast-food restaurants applying SSK. The interviews were transcribed verbatim and analysed using thematic analysis with the help of Nvivo software for analyse. Findings showed that among the motivations of consumers in using SSK are convenience, meeting needs, and alternative options. In conclusion, the findings of this research can facilitate existing restaurants in managing the technology applied and, at the same time, improve their service in offering a SSK to millennial customers.